MOTIVATION OF PRESCHOOL TEACHERS FOR PROFESSIONAL DEVELOPMENT IN THE FIELD OF FOSTERING EARLY CHILDHOOD DEVELOPMENT - Tanja Nedimović; Ivana Đorđev (Istraživanja u Pedagogiji, 2025)
The research presented in this paper was conducted in 2024 in the Autonomous Province of Vojvodina, Republic of Serbia. The aim of the study was to examine the level of preschool teachers' motivation for professional development in the field of fostering early childhood development (ECD) and to determine whether differences in motivation exist depending on years of work experience and level of education. Additionally, the study aimed to provide a broader insight into the frequency and methods of professional development that preschool teachers have undertaken in this field. The theoretical framework of the research is based on motivation theories (Herzberg’s two-factor theory of motivation and selfdetermination theory). In the context of preschool education reforms, professional development is crucial for implementing modern approaches in practice. The research had an exploratory character, and the sample was convenient (N = 91 preschool teachers). The data were analyzed using the SPSS statistical program, applying descriptive statistics (mean, standard deviation, frequencies, and percentages) and analysis of variance (ANOVA) to examine statistically significant differences. The results indicated a high level of motivation (4.37 on a five-point scale) among preschool teachers for professional development in fostering early childhood development. Statistically significant differences were found in selfassessed motivation based on years of work experience, F (3, 85) = 3.953, p = .011. Further analysis revealed that the level of education had a statistically significant impact on motivation for professional development, but only in the context of working with gifted children, F (4, 84) = 3.777, p = .007. Although participants expressed a high level of motivation, as many as 38.5% of preschool teachers reported that they had not yet engaged in professional development in this field, indicating a potential gap between declared motivation and its realization. The findings can contribute to improving educational practices and professional development strategies, serving as a foundation for developing various forms of training and enhancing higher education for future preschool teachers. Additionally, the study opens avenues for further research aimed at fostering the well-being of children in early childhood.